2007
DOI: 10.1111/j.1365-2036.2007.03579.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proton pump inhibitors on markers of risk for high‐grade dysplasia and oesophageal cancer in Barrett’s oesophagus

Abstract: SUMMARY BackgroundIt has been shown that the presence on diagnosis of endoscopic macroscopic markers indicates a high-risk group for Barrett's oesophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 30 publications
2
36
0
1
Order By: Relevance
“…This may provide additional experimental evidence for the necessity of continued acid suppression. Patients with dysplastic BE are reported to show a reversal of the dysplastic process by proton pump inhibitor therapy; [66][67][68] however, it is unknown if the lesions will reoccur once such a treatment is stopped.…”
Section: Discussionmentioning
confidence: 99%
“…This may provide additional experimental evidence for the necessity of continued acid suppression. Patients with dysplastic BE are reported to show a reversal of the dysplastic process by proton pump inhibitor therapy; [66][67][68] however, it is unknown if the lesions will reoccur once such a treatment is stopped.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 In addition, in one study, a delay in using a PPI for 2 years or more after diagnosis with BE was associated with an increased risk of developing LGD and an increased risk of developing HGD or EAC. 43 However, other studies have suggested that treatment with PPI or other acid-suppressing drugs was associated with an increased risk of EAC. 44,45 While PPIs may reduce the rate of progression in some patients with BE, they also induce significant hypergastrinemia in a subset of patients by reducing acid-inhibitory feedback pathways.…”
Section: Importance Of Inflammation and Bile Acidsmentioning
confidence: 99%
“…Epidemiological studies have shown that the long-term use of PPIs is associated with lower rates of dysplasia and EAC in patients with BE [122,124,[129][130][131], except for one study [132]. In two other studies, the early use of a PPIs after the diagnosis of BE was associated with a decreased risk of developing dysplasia or EAC [122,129] ( Table 4).…”
Section: Neoplastic Preventionmentioning
confidence: 99%
“…In two other studies, the early use of a PPIs after the diagnosis of BE was associated with a decreased risk of developing dysplasia or EAC [122,129] ( Table 4). The available data are insufficient to draw any definite conclusions [133,134].…”
Section: Neoplastic Preventionmentioning
confidence: 99%